Evaluation of the optical density of composite resins with the use of nanotechnology by means of intraoral radiographic system (CMOS) - Lilian Cristina Vessoni Iwaki; Flavia Martins Lacerda; Mariliani Chicarelli da Silva; Carina Gisele Costa Bispo; Wilton Mitsunari Takeshita (Universidade Estadual de Maringá, 2015)
The aim of this study was  investigate the optical density of four different brands of composite resins of nanotechnology. The composite resins Estelite Sigma Quick® (Tokuyama), Esthet -X HD® (Dentsply), 4 Seasons® (Ivoclar Vivadent) and Filtek Z350XTTM (3M-ESPE) were inserted into cavities in transparent acrylic sheets, separated by thickness into 1, 2 and 3 mm. The images were imported into the software ImageTool® 3.0 (UTHSCSA, EUA). Data were submitted to ANOVA and Tukey. The mean values of the composite resins 4 Seasons® (2.71±0.20) and Filtek Z350XTTM (2.64±0.26) did not differ statistically for samples with thickness of 1 and 2 mm. However, for both thickness Estelite Sigma Quick® (1.92±0.11) and Esthet-X HD® (3.57±0.29) showed significant differences compared to the other composite resins (p = .012). All 3 mm-thick samples showed significant differences among themselves (Estelite Sigma Quick® p < .001, Esthet-X HD® p < .001, 4 Seasons® p=.001 and Filtek Z350XTTMp = .003). Conclusion: Among the three thicknesses evaluated, Estelite Sigma Quick® showed the lowest optical density, whereas the highest values were observed for Esthet X HD®. The resins are studied according to the rules of optical density value thus being favorable clinical use.